Predictive efficacy of violence risk assessment instruments in Latin-America - Folino, Jorge Oscar (2015)
In Latin America, violence risk assessment used to be based in the non-structured clinical approach. An Argentinian cohort study that included violence risk assessment tools changed the tradition. The objective of this study is to inform of the observed predictive efficacy of these tools in the follow-up until March 2012. One hundred and fifty three consecutive pre-released convicted males were recruited from September 2001 through September 2004 in La Plata, Argentina. The pre-release assessment measures included the Hare Psychopathy Checklist-Revised, Assessing Risk for Violence V2, Structured Professional Judgment, and Violence Risk Appraisal Guide. The mean follow-up time was 1,290 days. Ninety-nine (64.7%) subjects had at least one general relapse, and 91 (59.5%) had at least one violent relapse. The incidence rate of violent recidivism was 16.8 per 100 person-years. While some indicators of predictive validity had no clinical significance, the time-dependent indicators did have clinical significance.